2010
DOI: 10.1021/op100199t
|View full text |Cite
|
Sign up to set email alerts
|

Initial Scale-Up and Process Improvements for the Preparation of a Lead Antibacterial Macrolone Compound

Abstract: Macrolones are a novel class of potent antimicrobial agents that consist of a macrolide scaffold to which a quinolone unit is tethered by various linkers to the 4′′-O-position of the cladinose sugar. In this paper is described a modified 13-step route to a lead compound in the series. Critical reaction steps in the medicinal chemistry route were modified for an initial scale-up process, and as a result, a synthetic procedure suitable for preparation of multihundred gram quantities of the final product, with 98… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 10 publications
0
4
0
2
Order By: Relevance
“…s dva dušika u veznom lancu, 19 dok su se kasnije pokazali bolji s jednim ili više kisika. 20,21,22,23 S kolegama iz Verone smo objavili još neke zaostale rezultate.…”
Section: Razdoblje 1996 -2003 Godine Prijelaz Na Bazična Istraživanunclassified
See 1 more Smart Citation
“…s dva dušika u veznom lancu, 19 dok su se kasnije pokazali bolji s jednim ili više kisika. 20,21,22,23 S kolegama iz Verone smo objavili još neke zaostale rezultate.…”
Section: Razdoblje 1996 -2003 Godine Prijelaz Na Bazična Istraživanunclassified
“…Velik dio praktičnih savjeta u svezi s poboljšanjem uvjeta reakcija publiciran je u radu objavljenom u Organic Process Research and Development, koji je napisao Vlado Štimac, 21 glavni nositelj uspješnog uvećanja postupka na univerzalni kemijski reaktor obujma 5 litara.…”
Section: Vanjski Suradnikunclassified
“…Moreover, because many quinolone candidates have been tested in the clinic, the effective syntheses of these compounds has become the focus of process chemistry initiatives. [1][2][3][4][5] While crystallization from solution is an established technique for the separation and purification of organic compounds, challenges arising from the complex interactions of variables including polymorphism, crystal nucleation and growth, and impurity profile are common. 6) For drug substances, understanding and controlling the polymorphism, particle size, morphology, and crystal habit have become fundamental steps in pharmaceutical development programs.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, 9a- N substituted 15-membered azalides with amide and amine functionalities also had marked advantages over azithromycin in terms of high selectivity for the bacteria and moderate oral bioavailability in vivo [ 9 , 14 , 15 , 16 ]. Besides, with intensive research of azithromycin, a novel modified measure of the 4″-position of the cladinose was potent against emergence of drug resistance [ 17 , 18 , 19 , 20 , 21 ]. To resolve these therapeutic problems of tolerance, we investigated and found that the 3- O -acylerythromycin derivatives, which were named ‘acylides’, not only recovered the abolished antibacterial activity but also enhanced pharmacological activity against resistant pathogens [ 22 ].…”
Section: Introductionmentioning
confidence: 99%